The CagRS Two-Component System Regulates Clavulanic Acid Metabolism via Multiple Pathways in Streptomyces clavuligerus F613-1 - Fu, Jiafang; Qin, Ronghuo; Zong, Gongli; Liu, Cheng; Kang, Ni; Zhong, Chuanqing; Cao, Guangxiang (Frontiers in Microbiology, 2019)
Streptomyces clavuligerus F613-1 produces a clinically important β-lactamase inhibitor, clavulanic acid (CA). Although the biosynthesis pathway of CA has essentially been elucidated, the global regulatory mechanisms of CA biosynthesis remain unclear. The paired genes cagS and cagR, which are annotated, respectively, as orf22 and orf23 in S. clavuligerus ATCC 27064, encode a bacterial two-component regulatory system (TCS) and were found next to the CA biosynthetic gene cluster of S. clavuligerus F613-1. To further elucidate the regulatory mechanism of CA biosynthesis, the CagRS TCS was deleted from S. clavuligerus F613-1. Deletion of cagRS resulted in decreased production of CA, but the strain phenotype was not otherwise affected. Both transcriptome and ChIP-seq data revealed that, in addition to CA biosynthesis, the CagRS TCS mainly regulates genes involved in primary metabolism, such as glyceraldehyde 3-phosphate (G3P) metabolism and arginine biosynthesis. Notably, both G3P and arginine are precursors of CA. Electrophoretic mobility shift assays demonstrated that the response regulator CagR could bind to the intergenic regions of argG, argC, oat1, oat2, ceaS1 and claR in vitro, suggesting that CagR can directly regulate genes involved in arginine and CA biosynthesis. This study indicated that CagRS is a pleiotropic regulator that can directly affect the biosynthesis of CA and indirectly affect CA production by regulating the metabolism of arginine and G3P. Our findings provide new insights into the regulation of CA biosynthetic pathways and provide an innovative approach for future metabolic engineering efforts for CA production in S. clavuligerus.